Potret Gerakan Pemberdayaan Perempuan pada Kelompok Yasinan di Desa Winong Perspektif Feminisme Fatimah Mernissi - Setiabudi, Moh. Nuzul; Mulia Ardi (Az-Zahra: Journal of Gender and Family Studies, 2025)
This article discusses the shifting gender roles in religious practices traditionally dominated by men, a phenomenon that often triggers inequality. This situation has led to the emergence of the yasinan movement, a women's initiative that serves as a form of emancipation and a rejection of the marginalization of their roles in socio-religious spaces. This descriptive qualitative research adopts a case study approach on the yasinan women's congregation in Winong Village, Tulungagung Regency. Data were collected through participant observation, in-depth interviews, and literature review. The analysis was conducted using a hermeneutic-philosophical method, with the feminist perspective of Fatima Mernissi as the main analytical framework. The findings reveal two crucial points. First, Fatima Mernissi’s thought opens up new interpretative spaces for gender equality, highlighting the urgency for women to fight for their rights in order to achieve equality and justice in religious and cultural spheres. Second, the yasinan activities in Winong Village significantly reconstruct traditional religious practices as a gateway toward gender equality, particularly through informal education and the strengthening of women’s rights awareness. This study implies that community-based religious movements led by women have great potential as agents of social change, challenging patriarchal norms and promoting gender equality from the grassroots level within a deeply rooted cultural context.